Menguak Peran dan Tantangan Advokat dalam Sistem Peradilan Pidana Indonesia: Suatu Kajian Praktis - Rahaman Upara, Abdul; Mochammad Roem, Anwar (Universitas Ekasakti, 2023)
This article delves deeply into the role played by lawyers in the context of the Indonesian criminal justice system. Through a practical study, this research analyzes the contributions of lawyers to the sustainability of the criminal justice system while highlighting the challenges they face in carrying out their duties. This research approach involves the examination of specific cases, interviews with lawyers, and a review of recent legislative changes. The analysis underscores how lawyers not only function as legal advocates for defendants but also have a significant impact on the integrity, transparency, and efficiency of the criminal justice system. The main challenges faced by lawyers, including resource limitations, time pressure, and various regulatory aspects, are detailed and explored. The findings of this study provide in-depth insights for legal practitioners, policymakers, and academics regarding the complex dynamics of lawyers in the context of Indonesian criminal justice. Practical implications and recommendations for system improvement are also discussed as positive contributions from this research.